Updating Gender in Electronic Medical Records - A Commentary - Ben Andert (University of North Florida, 2017)
It is argued in this commentary that many patient intake and permanent medical record forms make archaic assumptions about use of the word "gender." A further argument is made for change that accounts for the needs of persons who do not readily identify as "male" or "female." Several suggestions for making such accommodations available are offered.